An advanced approach to predicting optimal material compositions for graphene/carbon black reinforced polypropylene/polyvinyl chloride nanocomposites focusing mechanical and economic performance - Utkarsh Patil; Pravin Kubade (Polyolefins Journal, 2025)
The growing need for enhanced materials has led to the development of nanocomposites, which have shown great potential in various industries. However, optimizing the composition of these materials to achieve the best mechanical performance and cos t-effectiveness remains a challenge. This research addresses this challenge by employing a virtual experimental approach, utilizing Digimat for material modeling and CATIA for design and finite element analysis (FEA). This approach allows for the simulation and analysis of different nanocomposite compositions without the need for costly and time-consuming physical experiments. The study focuses on Polypropylene (PP) and polyvinyl chloride (PVC) based nanocomposites with graphene and carbon black reinforcements. The research investigates the impact of varying the weight percentages of these nanofillers on the mechanical properties of the composites. The PP/PVC blends are created in different weight ratios to provide further compositional control. The material preparation is carried out in Digimat, where the properties of the composites are defined using a micromechanical model. The FEA is then conducted in CATIA, where a standard AS TM D638 tensile specimen is simulated under controlled conditions. The results are validated by varying mesh sizes to optimize deflection and Von Mises s tress predictions. Furthermore, an economic analysis is conducted to evaluate the cos t-effectiveness of the different nanocomposite compositions. The study highlights the importance of virtual experimentation in materials science, as it allows for efficient exploration of various material compositions and reduces the need for physical prototyping. This approach accelerates the material development process and enables the optimization of material design for specific applications. The virtual trials explored alternatives to PVC using PP-based composites reinforced with graphene/carbon black. PP/PVC 40/60 reinforced with 1.5% wt. graphene (P4V6G15) and reinforced with 7.5% wt. carbon black (P4V6C75) showed 31.6% and 31.2% deflection reductions compared to pure PP, respectively. These results show that P4V6 blends, especially those with graphene or high carbon black concentrations, serve as promising alternatives to conventional PVC. Among them, P4V6C75 stands out by offering the best overall mechanical performance. It also provides the lowest production cos t. In terms of economic favorability, P4V6C75 is approximately 2.55 times more cos t-effective than the graphene-based blend P4V6G15. This combination of high performance and low cos t makes P4V6C75 the most suitable candidate for PVC replacement.